Qualitative and Quantitative Phytochemical Constituents, Antioxidant Activities, and Antimicrobial Studies of Methanol Extract of Morinda citrifolia Stem - Ogbeide, Osahon Kennedy; Aghedo, Oscar Notoriuwa; Akhidenor, Faith Isimemen; Dibie, Edward Nduka; Iyasele, Julius Uche (Sciences of Phytochemistry, 2025)
This study evaluated the qualitative and quantitative phytochemical constituents, antioxidant potential, and antimicrobial properties of Morinda citrifolia stem. The stem extract was prepared using the maceration method with 99.8% methanol for three days at room temperature. Phytochemical and proximate compositions were analyzed using standard methods, while selected minerals were determined by atomic absorption spectrophotometry. Antioxidant activity was assessed using the DPPH free radical scavenging assay, and antimicrobial activity was examined by the agar-well diffusion method. Phytochemical screening revealed the presence of phenolics, glycosides, steroids, terpenoids, alkaloids, tannins, flavonoids, and eugenols. Proximate analysis showed moisture, lipid, protein, ash, fiber, and carbohydrate contents of 18.99%, 9.12%, 4.72%, 6.40%, 37.90%, and 22.87%, respectively. The concentrations of Na, Mg, K, Ca, Fe, Cu, and Zn were 7.51 ± 1.60, 126.67 ± 9.43, 91.12 ± 16.12, 7.59 ± 0.63, 3.50 ± 0.65, 0.02 ± 0.003, and 0.26 ± 0.086 mg/kg, respectively. The extract exhibited strong antioxidant activity with an IC₅₀ of 49.48 µg/mL, comparable to ascorbic acid (46.56 µg/mL). Antimicrobial testing showed inhibition of Staphylococcus aureus growth, with minimum inhibitory and bactericidal concentrations of 500 mg/mL and 50–200 mg/mL, respectively. These results demonstrate that M. citrifolia stem methanol extract possesses significant antioxidant and antimicrobial activities, supporting its potential as a natural therapeutic and its traditional medicinal applications.